A microstrip grid array antenna for 24 GHz Doppler sensors - Lin, Zhang. (2013)
A single feed grid array antenna for 24 GHz Doppler sensor is proposed in this paper. It is designed on 0.787 mm thick substrate made of Rogers Duroid 5880 (εr= 2.2 and tan δ= 0.0009) with 0.017 mm copper claddings. Dimension of the antenna is 60 mm × 60 mm × 0.787 mm. This antenna exhibits 2.08% impedance bandwidth, 6.25% radiation bandwidth and 20.6 dBi gain at 24.2 GHz. The beamwidth is 14°and 16°in yoz and xoz planes, respectively.